Solution of topical spectroradiometric problems using synchrotron radiation - A. S. Sigov; N. B. Golovanova; O. A. Minaeva; S. I. Anevsky; R. V. Shamin; O. I. Ostanina (Российский технологический журнал)
Objectives. In order to solve fundamental metrological problems concerning the reproduction and transmission of spectral radiometry units, as well as developing methods and tools for metrological support of modern technologies such as nanophotolithography in the electronics industry, synchrotron radiation can be used. When developing solid-state sources and receivers of radiation, new topical problems arise in connection with the metrological characteristics of light-emitting diodes (LEDs), multi-element array receivers, charge-coupled device (CCD) cameras and telescopes, whose successful solution depends on the properties of a reference source of synchrotron radiation. Therefore, the purpose of the present work is to develop spectral radiometry methods for obtaining metrological channels using an electron storage ring in order to control the characteristics of electronics components, as well as for studying and calibrating radiometers, photometers, and emitters operating in the visible, ultraviolet and infrared regions of the electromagnetic spectrum.Methods. Methods for transmitting spectroradiometric units on an electron storage ring are based on the classical theory of Julian Schwinger, which describes the electromagnetic radiation of a relativistic electron to calculate the spectral and energetic synchrotron radiation characteristics taking polarization components into account.Results. The possibility of developing methods for transmitting spectral radiometric units using synchrotron radiation was evaluated by means of a test setup, which included a monochromator-based comparator, a telescope with a CCD array, a spectroradiometer, a radiometer, a photometer, a goniometer, and an integrating sphere. This allowed the full set of spectroradiometric and photometric characteristics of radiation sources and receivers to be measured: from the most differential distribution of the spectral radiance density of the emitting region to the integral radiation flux. The results were compared with the reference synchrotron radiation source.Conclusions. Among possible approaches for determining the metrological characteristics of LED emitters, multielement array receivers, CCD cameras, and telescopes, synchrotron radiation seems to be the most promising. This approach allows the small size of the emitting region of synchrotron radiation, the Gaussian distribution of radiance over the emitting region of the synchrotron electron bunch, as well as the wide dynamic range of spectrum tuning due to changes in the energy and number of accelerated electrons, to be taken into account.